How scaffolds shape MAPK signaling: what we know and opportunities for systems approaches - Witzel, Franziska; Maddison, Louise E.; Blüthgen, Nils (Frontiers in Physiology, 2012)
Scaffolding proteins add a new layer of complexity to the dynamics of cell signalling. Above their basic function to bring several components of a signalling pathway together, recent experimental research has found that scaffolds influence signalling in a much more complex way: Scaffolds can exert some catalytic function, influence signalling by allosteric mechanisms, are feedback-regulated, localise signalling activity to distinct regions of the cell or increase pathway fidelity. Here we review experimental and theoretical approaches that address the function of two MAPK scaffolds, Ste5, a scaffold of the yeast mating pathway and Ksr1/2, a scaffold of the classical mammalian MAPK signalling pathway. For the yeast scaffold Ste5, detailed mechanistic models have been valuable for the understanding of its function. For scaffolds in mammalian signalling, however, models have been rather generic and sketchy. For example, these models predicted narrow optimal scaffold concentrations, but when revisiting these models by assuming typical concentrations, rather a range of scaffold levels optimally supports signalling. Thus, more realistic models are needed to understand the role of scaffolds in mammalian signal transduction, which opens a big opportunity for systems biology.